Charge-transfer-solvent interaction predefines doping efficiency in p-doped P3HT films - Müller, Lars; Nanova, Diana; Glaser, Tobias; Beck, Sebastian; Pucci, Annemarie; Kast, Anne K.; Schröder, Rasmus R.; Mankel, Eric; Pingel, Patrick; Neher, Dieter; Kowalsky, Wolfgang; Lovrincic, Robert (Chemistry of materials, 2016)
Efficient electrical doping of organic semiconductors is a necessary prerequisite for the fabrication of high performance organic electronic devices. In this work, we study p-type doping of poly(3-hexylthiophene) (P3HT) with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) spin-cast from two different solvents. Using electron diffraction, we find strong dopant-induced π-π-stacking for films from the solvent chloroform, but not from chlorobenzene. This image is confirmed and expanded by the analysis of vibrational features of P3HT and polaron absorptions using optical spectroscopy. Here, a red-shifted polaron absorption is found in doped films from chloroform, caused by a higher conjugation length of the polymer backbone. These differences result in a higher conductivity of films from chloroform. We use optical spectroscopy on the corresponding blend solutions to shed light on the origin of this effect and propose a model to explain why solutions of doped P3HT reveal more aggregation of charged molecules in chlorobenzene, whereas more order is finally observed in dried films from chloroform. Our study emphasizes the importance of solvent parameters exceeding the bare solubility of pure dopant and host material for the preparation of highly conductive doped films.